What factors contribute to uncontrolled gout and hospital admission? A qualitative study of inpatients and their primary care practitioners - Darren Chyi Hsiang Kong; Elizabeth Ann Sturgiss; Annamma Kochummen Dorai Raj; Kieran Fallon (BMJ Open)
Objective To provide deeper insight into why patients are admitted to hospital with gout and discover potential targets for better disease control.Design Data from semi-structured interviews were analysed using a thematic analysis approach.Participants and setting Eleven inpatients from a tertiary institution in the Australian Capital Territory of Australia and their respective general practitioners (GPs) were invited to participate in the semi-structured interviews.Results Despite significant pain and disability that accompanied acute flares, patients continue to experience shame in seeking treatment and regarded gout as being not particularly important. Other barriers included patients’ poor continuity of care with and lack of confidence in GPs, suboptimal management in outpatient and inpatient settings, poor understanding of disease and treatment, and misconceptions held by both patients and physicians leading to uncontrolled disease activity.Conclusions Barriers to optimal gout management including patient and health practitioner factors have produced a complex effect which has led to a cycle of treatment avoidance behaviours and recurrent hospitalisations for severe acute gout flares. These barriers could be addressed using a multipronged approach guided by the chronic care model which has been applied in a variety of other chronic diseases with improved patient and professional-level outcomes. Managing gout according to best practice for chronic disease is more likely to prevent recurrent hospitalisations and improve health outcomes in patients with gout.